Effect of Stocking Density on Growth, Survival and Production Performances of Clarias Batrachus Fry in Nursery Hapa Under Semi-intensive Culture System of Rajshahi University Campus, Bangladesh - Aktar, Mst Rima Aktar; Khanom, Dil Afroza Khanom; Hossain, Md Delwer Hossain (Journal of Bio-Science, 2023)
An experiment was conducted to assess the effect of stocking density on growth, survival and production performance of Clarias batrachus (Magur) fry using nursery hapa in experimental pond of Dept. of Fisheries, University of Rajshahi. The research was carried out for a period of three months from May to July, 2021 consisting of four treatments each with two replications. A total of eight hapa were prepared using net each having an area of 1.2 × 0.9 × 0.9 m3. Stocking density was maintained at the rate of 300, 350, 400 and 450 fry ∕ m3 in T1, T2, T3 and T4 respectively where the mean initial weight of hatchling was 0.04±0.01 g. Different physico-chemical parameter of water were monitored fortnightly where the mean value of water temperature, water transparency, dissolved oxygen, carbon dioxide, PH and NH3-N was observed 28.25±1.18°C, 26.12±0.18 cm, 8.44±0.45 mg/l, 1.78±0.03 mg/l, 6.88±0.04 and 0.007± 0.00 mg/l respectively. Except NH3-N no significant difference (p˃0.05) was found among the treatments and all the parameter were in suitable range for fry rearing. Highest mean final weight, weight gain, SGR (%/day), survival rate, along with lower FCR was found in T1 which was 8.00±0.13 g, 7.96±0.07 g, 5.65±0.00 (%/day) and 91±0.70 (%) respectively followed by T2, T3 and T4 where significant variation (p˂0.05) was found among them. Maximum net yield (kg/m3/90 days) was 2.51±0.07 which was obtained from T3 followed by 2.48±0.02, 2.37±0.02 and 2.20±0.05 in T4, T2 and T1. On the other hand, benefit cost ratio (BCR) was found significantly higher (p˂0.05) in T1 (0.73±0.01) than T2 (0.66 ±0.01), T3 (0.56±0.00) and T4 (0.43±0.02). The overall result indicated that a stocking density of 300 fry/m3 (T1) could be more profitable for Clarias batrachus fry rearing in nursery hapa. J. Bio-Sci. 31(1): 17-27, 2023